2010
DOI: 10.1007/s00192-010-1218-x
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic pain in urogynaecology. Part I: evaluation, definitions and diagnoses

Abstract: Aim of this review is to summarise the available literature on the definitions and assessment of pelvic pain in the urogynaecological patient. A MEDLINE search and a hand search of conference proceedings of the International Continence Society and International Urogynecological Association were performed. Sixty-nine articles were reviewed. The site of pain was specified in 45% of the articles, 20% used the digital examination of pelvic myofascial trigger points for the diagnosis; 20%, the Pelvic Pain and Urgen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 77 publications
0
16
0
Order By: Relevance
“…A wide variety of painful somatic and visceral disorders are associated with the female reproductive tract . Dysmenorrhea has been described as one of the most common complaints in gynecological practice with a prevalence rate as high as 90% .…”
Section: Introductionmentioning
confidence: 99%
“…A wide variety of painful somatic and visceral disorders are associated with the female reproductive tract . Dysmenorrhea has been described as one of the most common complaints in gynecological practice with a prevalence rate as high as 90% .…”
Section: Introductionmentioning
confidence: 99%
“…Such events can be the preexisting trauma that leads to future myofascial dysfunction (Doggweiler‐Wiygul, ; Montenegro, Vasconcelos, Candido Dos Reis, Nogueira, & Poli‐Neto, ; Simons et al, ). Women with CPP have reported more musculoskeletal impairments than women without CPP (Kavvadias, ; Tu, Holt, Gonzales, & Fitzgerald, ), and one group of researchers reported 85% of patients with CPP had musculoskeletal dysfunction and postural changes that contributed to their CPP (Montenegro et al, ). A commonly accepted hypothesis is that these musculoskeletal impairments cause muscular strain due to low‐level static exertion of the muscle during prolonged motor tasks, or result from mechanical factors creating muscle pain and injury (Henneman, Somjen, & Carpenter, ).…”
Section: Overview Of Myofascial Pelvic Painmentioning
confidence: 99%
“…Prevalence estimates range from as low as 14% to 23% of women with CPP have myofascial pelvic pain (Tu, As‐Sanie, & Steege, ) to as high as 78% among women with interstitial cystitis (Bassaly et al, ; Doggweiler‐Wiygul, ; Itza et al, ). In a recent review, researchers found that very few providers actually perform a vaginal digital palpation of pelvic floor muscles during routine gynecological exams to examine for the presence of myofascial pelvic pain and trigger points (Kavvadias, Baessler, & Schuessler, ). An estimated 10% to 15% of women's gynecologic consultations are secondary to CPP, and 40% of gynecologic laparoscopies are performed to determine a cause of CPP (Paulson & Delgado, ).…”
mentioning
confidence: 99%
“…[1,2] The diagnosis is usually made by exclusion of other lower urinary tract diseases, [3] and the underlying pathophysiology remains elusive despite extensive research by many investigators. Although multiple therapeutic approaches, such as dietary, behavioral, pharmacological, and interventional therapies, have been attempted, there is still no optimal treatment protocol for interstitial cystitis at present.…”
Section: Introductionmentioning
confidence: 99%